Heavy metal concentration in sediment during dry and wet seasons at Sungai Jarum Mas, Matang Mangroves Forest, Perak - Sulaiman, Nor Haslinda (2018)
Concentration of heavy metals varied depending on different seasons and sediment depths. The objectives of this study were to determine the physiochemical properties of sediment and compared the physiochemical properties in Sungai Jarum Mas by different seasons and sediment depths. Seasonal variation of sediment; EC, pH and heavy metals iron (Fe), lead (Pb), zinc (Zn), copper (Cu) and cadmium (Cd) were measured in sediment sampled along Sungai Jarum Mas, Perak. The dry and wet season samples were collected in June and December 2015 respectively. Heavy metal elements were analyzed using Atomic Absorption Spectrometer (AAS) machine. Data obtained were analyzed using Statistical Analysis System (SAS) version 9.4. The result showed that the sediment in Sungai Jarum Mas was acidic. The sediment EC, pH water and pH 1 M KCl were higher in dry season with a mean 16.28(±0.502), 3.48(±0.027) and 3.28(±0.024), respectively. Iron(Fe) was obtained at a higher concentration in the sediment during dry season with a mean 8.908(±1.140) Cmol/Kg. Both lead (Pb) and cadmium (Cd) had a mean concentration of 0.018(±0.00) and 0.001(±0.00) Cmol/Kg, respectively in both seasons. While copper (Cu) and zinc (Zn) were found to be the highest in wet season with a mean 0.185(±0.048) and 0.029(±0.008) Cmol/Kg, respectively. Fe, Pb and Zn were recorded within the permissible limit of heavy metals concentraton in soil set by the WHO (2008), while Cu and Cd exceeded the standards. In term of EPA (2002) guidelines, Sungai Jarum Mas was moderately polluted by Cu. Heavy metals present in sediment due to environmental and human-induced factors. The knowledge of heavy metal concentrations in marine sediment is very important with respect to environmental management, aquatic ecology and human health.